An energetically consistent heat input model for additive manufacturing - Burkhardt, Christian; Soldner, Dominic; Steinmann, Paul; Mergheim, Julia (Proceedings in Applied Mathematics and Mechanics, 2019)
Additive manufacturing offers the ability to design parts more freely and to realize complex geometries that would not have been manufacturable with conventional processes. In powder bed‐based beam melting processes parts are build in a layer‐by‐layer fashion by selectively melting the powder material to generate the part. The energy input of the laser beam and the temperature distribution during the process strongly influence the quality of the produced part and can be studied by means of macroscopic thermal simulations. Due to the non‐linearity of the material behaviour and the diverging time and length scales huge computational costs arise. In the present contribution a temporal integration of the heat input model is used to allow for larger time step sizes. In order to reduce the errors due to the spatial discretization in the heat affected zone, a correction term is introduced, rendering an energetically consistent heat input. A numerical example shows the success of this strategy.<br